Bread Wheat Germplasm Evaluation for Soil Moisture Stress Tolerance under Rainfed Condition - Kumar, Arvind; Sharma, P. C.; Singh, R.; Kumari, J. (International Journal of Bio-resource and Stress Management, 2018)
A preliminary yield trial was conducted with 1358bread wheat germplasm including four national checks (C-306, KRL 210, HD 2967 and Kharchia, 65) for identifying moisture stress tolerant genotypes. The experiment was conducted at experimental farm, Central Soil Salinity Research Institute, Karnal under rainfed conditions during 2015-16 cropping season. The new germplasm were compared against four standard varieties using an augmented design with fifteen blocks. Evaluation of germplasm accessions revealed considerable variation among grain yield (g)-m, effective tillers per meter and days to 50% heading traits studied. The adjusted grain yield of sixty two germplasm (38 accessions of NBPGR and 24 salt tolerant lines of CSSRI) were out yield the best check (C-306). However seventeen genotypes, namely, EC463441, EC534443, EC609338, IC543290, IC321905, IC535493, IC547643, KRS-611, KRL-112, KRL-105, KRL-136, KRL-119, KRS-621, KRL2-10, KRL-340, KRL-90 and KRL-35 were found most desirable for yield potential. These germplasm can be considered as an important source of genes for earliness, higher grain yield and for improving number of effective tillers in wheat improvement programme for drought tolerance. Non-significant differences for grain yield between the salt tolerant (KRL 210 and Kharchia 65) and drought tolerant (C-306) checks shows co-existence of salt and water stress tolerance in KRL 210 and Kharchia 65, although both the cultivars were developed for salt prone area, it is, as such, they are likely fit for cultivation under conditions with low soil moisture.